Analisis Kinerja Lembaga Pendidikan Dengan Balance Score Card: Studi Kasus Di Pondok Pesantren Thohir Yasin Lombok Timur - Junaidi, M; Iswandi, L.; Arfini, Bq. Desy (STAI Darul Kamal NW Kembang Kerang, 2025)
Competition in the world of education is currently getting tighter, and now educational institutions are competing to be able to provide the best educational services, in accordance with the expectations of the community. An institution is said to have a competitive advantage when the institution has something that its competitors do not have, does something better than other institutions, or is able to do something that other institutions are not able to do. This study uses a qualitative research method with observation, interview and documentation data collection techniques. Data analysis uses data reduction, data display, and conclusion drawing methods. The results of the study show that performance measurement at the Thohir Yasin Islamic Boarding School, East Lombok, found results based on the balance scorecard perspective, namely: 1) customer perspective, by paying attention to customers. 2) financial perspective, with regular financial management showing that the finances at the Thohir Yasin Islamic Boarding School are well managed. 3) internal business perspective, shown by various innovations that have been made in carrying out its function as an educational service provider. 4) growth and learning perspective, by starting to prepare quality resources, physical development facilities and modern learning media.